2018
DOI: 10.1364/ol.43.001131
|View full text |Cite
|
Sign up to set email alerts
|

Laser wakefield acceleration with mid-IR laser pulses

Abstract: We report on, to the best of our knowledge, the first results of laser plasma wakefield acceleration driven by ultrashort mid-infrared (IR) laser pulses (λ=3.9  μm, 100 fs, 0.25 TW), which enable near- and above-critical density interactions with moderate-density gas jets. Relativistic electron acceleration up to ∼12  MeV occurs when the jet width exceeds the threshold scale length for relativistic self-focusing. We present scaling trends in the accelerated beam profiles, charge, and spectra, which are support… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…For the wavelength scaling of laser-based acceleration of electrons to maximum energy by LWFA (laser wake field acceleration) the situation is more complicated, since many parameters have to be considered [257] . Nevertheless it was shown that the larger plasma structures are capable of accelerating bunches of higher charges [258] . Another application of high laser intensities is the generation of high harmonics (HHG), where the high-energy cutoff also scales with I λ 2 , with the macroscopic scaling ω ∼ λ 1.6 -λ 1.7 .…”
Section: The Development Of Mid-infrared Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…For the wavelength scaling of laser-based acceleration of electrons to maximum energy by LWFA (laser wake field acceleration) the situation is more complicated, since many parameters have to be considered [257] . Nevertheless it was shown that the larger plasma structures are capable of accelerating bunches of higher charges [258] . Another application of high laser intensities is the generation of high harmonics (HHG), where the high-energy cutoff also scales with I λ 2 , with the macroscopic scaling ω ∼ λ 1.6 -λ 1.7 .…”
Section: The Development Of Mid-infrared Lasersmentioning
confidence: 99%
“…For the wavelength scaling of laser-based acceleration of electrons to maximum energy by LWFA (laser wake field acceleration) the situation is more complicated, since many parameters have to be considered [257] . Nevertheless it was shown that the larger plasma structures are capable of accelerating bunches of higher charges [258] .…”
Section: Future Technologiesmentioning
confidence: 99%
“…Such performances have been reached in laser-solid experiments [16,17].Besides, mid-and far-infrared light sources supplying TW peak powers are today available. Femtosecond laser facilities with 3.9 µm central wavelength opened the way to multi-octave supercontinuum generation [18] and can accelerate electrons to 12 MeV energy in gas jets [19]. CO 2 lasers (λ 0 = 10.6 µm) are also operational in the ps range [20] and they should soon provide revolutionary tools unveiling new regimes in particle acceleration and future colliders [21].…”
mentioning
confidence: 99%
“…2(f)] promote particle injection. Using longer laser wavelengths also favors selffocusing for peak powers above critical, P > P c = 17(λ p /λ 0 ) 2 [GW], and increases the charge of the accelerated electron bunch [19]. Figure 4(a) shows the maximum normalized laser electric field along the propagation axis for the three studied wavelengths.…”
mentioning
confidence: 99%
“…The development of mid-infrared (IR) ultrafast pulsed lasers of high intensity, short pulse duration and tunable carrier wavelength at 2.0-5.0 µm is of great interest for a diverse range of applications from high harmonic generation [1,2] and laser wakefield acceleration [3,4] to spectroscopic investigation [5,6] . Owing to the lack of proper gain media, nonlinear down-conversion is a common method to generate the intensive mid-IR pulsed laser, which is inaccessible by a mode-locked laser.…”
Section: Introductionmentioning
confidence: 99%